Commodification through Exaggerated Narratives in Indonesian YouTube Industry: Capital Maintenance & Reputation - Azzumar Adhitia Santika; Yasmin Alvina (Journal of Communication and Public Relations, 2025)
Recent commodification studies primarily focus on what is commodified, often overlooking how it is delivered through exaggerated narratives within the Indonesian YouTube industry. Using Vincent Mosco's work on commodification, this qualitative research aims to analyze how Atta Halilintar (AH), a prominent figure and one of the biggest powers in the industry, employs exaggerated narratives as a deliberate tool for commodifying information into exchange value, specifically to make the content more appealing and entertaining. The data of this research were gathered from the four most-viewed of AH's ‘Grebek Rumah’ videos. We use multimodal critical discourse analysis (MCDA) to analyze the data from its titles, thumbnails, photography compositions, and conversations. The results show that exaggerated narratives cannot only be seen as a deliberate tool to make content more appealing and entertaining. Beyond that, this tool also has capital interests and follows market logic. This means content that might be perceived as inappropriate will continue to be produced as long as it is still widely consumed/watched. However, unethical use of this tool, such as intentionally presenting misleading information, can damage the creator's reputation. Thus, the digital content creators must be aware of and use this deliberate tool ethically, rather than only focusing on maximizing capital potential. For theoretical contributions, we suggest exaggerated narratives to be considered as an important aspect in content commodification, and suggest future research to pay more attention to its use in other platforms.